GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 16361 species occurrences available in GBIF matching the query: TaxonKey: Pertusaria pertusa (Weigel) Tuck. HasCoordinate: TRUE HasGeospatialIssue: FALSE. The dataset includes 16361 records from 86 constituent datasets: 3 records from Jordal. 35 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 102 records from BLS Lichen Database: Welsh churchyards. 95 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 43 records from HBRG Fungus, Lichen & Lower Plants Dataset. 4 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 1 records from PlutoF platform observations. 2 records from PRECIS. 40 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 16 records from Lichen diversity in forests. 22 records from BioFokus. 750 records from Artdata. 11 records from OHN. 1 records from Données ONF Faune-Flore-Fonge. 1359 records from BLS Lichen Database: English churchyards. 10 records from Australia's Virtual Herbarium. 1 records from Estonian Museum of Natural History. 1 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 9 records from naturgucker. 4 records from Erik Acharius lichen collection. 1 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 5 records from National Trust - Hatfield Forest species data held by The National Trust.. 6 records from Dutch Vegetation Database (LVD). 4 records from Rådgivende Biologer. 90 records from Lichen herbarium, NTNU University Museum. 82 records from Lichen herbarium, Oslo (O). 4 records from Dorset Sites of Nature Conservation Interest (SNCI) species records 2000-2008. 3 records from IBF Monitoring of Lichens. 1 records from The Lichen Collection at the Botanische Staatssammlung München. 12 records from BRERC species records recorded over 15 years ago. 5 records from Natural History Museum (London) Collection Specimens. 6 records from Ireland's BioBlitz. 11 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 18 records from Herbarium Senckenbergianum (FR) - Fungi. 3317 records from BLS Lichen Database: Scotland. 22 records from Real Jardin Botanico, Madrid: MA-Lichen. 3 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 1 records from Kystfuruskoger 2015. 3 records from Michigan State University Herbarium Lichens. 22 records from Arizona State University Lichen Collection. 9 records from Botanical Museum, Copenhagen, the Lichen Herbarium. 63 records from Danish Mycological Society, fungal records database. 96 records from Lichen Herbarium Berlin. 79 records from Biologiezentrum Linz. 104 records from LiquenCAT: Banco de datos de los líquenes de Cataluña. 24 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 28 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 8 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Verified data. 51 records from Universitat de València, Colecciones de Criptógamas: VAL_Lich. 146 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 1 records from Zukünftiges NSG Höftland/Bockholmwik. 1 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 3 records from Lichens of North-Eastern Poland. 54 records from Natural History Museum, University of Tartu. 1 records from Lichens of Biebrza National Park. 16 records from Herbarium of Umeå University (UME). 4214 records from BLS Lichen Database: England. 1 records from Weevils of Wales and England. 21 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 61 records from Biological and palaeontological collection and observation data MNHNL. 4 records from E39 Lyngdal - Ålgård. 3454 records from BLS Mapping Scheme dataset, 1750-2009. 969 records from BLS Lichen Database: Wales. 1 records from Wetland Inventory (NV). 7 records from ARKO gamle edellauvtrær. 194 records from Lund Botanical Museum (LD). 1 records from National Trust - Ickworth species data held by The National Trust.. 2 records from Field Museum of Natural History (Botany) Lichen Collection. 102 records from Norwegian Species Observation Service. 7 records from Lichens of Knyszyn Forest. 27 records from LNHG Biological Records Dataset. 12 records from Lichen herbarium, NMBU. 4 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 1 records from Données ONF Faune-Flore-FOnge. 8 records from Lichen field notes, Oslo (O). 2 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 74 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 2 records from Lichen herbarium, Tromsø Museum. 7 records from National Trust for Scotland Species Records. 9 records from Geneva Herbarium – General Collection (G). 17 records from BRERC species records within last 15 years. 111 records from Lichen herbarium, UiB. 236 records from Fungi (S). 2 records from John Muir Trust - Knoydart Lichens, 1990. 1 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences